A robust and reliable non-invasive test for stress responsivity in mice - Zimprich, Annemarie; Garrett, Lillian; Deussing, Jan M.; Wotjak, Carsten T.; Fuchs, Helmut; Gailus-Durner, Valerie; de Angelis, Martin Hrabě; Wurst, Wolfgang; Hölter, Sabine M. (Frontiers in Behavioral Neuroscience, 2014)
Stress and an altered stress response have been associated with many multifactorial diseases, such as psychiatric disorders or neurodegenerative diseases. As currently mouse mutants for each single gene are generated and phenotyped in a large-scale manner, it seems advisable also to test these mutants for alterations in their stress responses. Here we present the determinants of a robust and reliable non-invasive test for stress-responsivity in mice. Stress is applied through restraining the mice in tubes and recording behavior in the Open Field 20 min after cessation of the stress. Two hours, but not 15 or 50 min of restraint lead to a robust and reproducible increase in distance traveled and number of rearings during the first 5 min in the Open Field in C57BL/6 mice. This behavioral response is blocked by the corticosterone synthesis inhibitor metyrapone, but not by RU486 treatment, indicating that it depends on corticosteroid secretion, but is not mediated via the glucocorticoid receptor type II. We assumed that with a stress duration of 15 min one could detect hyper-responsivity, and with a stress duration of 2 h hypo-responsivity in mutant mouse lines. This was validated with two mutant lines known to show opposing effects on corticosterone secretion after stress exposure, corticotropin-releasing hormone (CRH) over-expressing mice and CRH receptor 1 knockout (KO) mice. Both lines showed the expected phenotype, i.e., increased stress responsivity in the CRH over-expressing mouse line (after 15 min restraint stress) and decreased stress responsivity in the CRHR1-KO mouse line (after 2 h of restraint stress). It is possible to repeat the acute stress test several times without the stressed animal adapting to it, and the behavioral response can be robustly evoked at different ages, in both sexes and in different mouse strains. Thus, locomotor and rearing behavior in the Open Field after an acute stress challenge can be used as reliable, non-invasive indicators of stress responsivity and corticosterone secretion in mice.